Pengaruh persepsi kemudahan kemanfaatan pengguna Sistem Informasi Direktorat Jenderal Pajak (SIDJP) terhadap kinerja pegawai - Kiki Hardiyanti Danial; Veronika Sari Den Ka; Imron Burhan (Income Journal: Accounting, Management and Economic Research, 2022)
This study aims to determine effect of perceived ease of use and usefulness of the use of the Sistem Informasi Direktorat Jenderal Pajak (SIDJP) on the performance employees of KPP Pratama Makassar Utara. Sampling was carried out by convenience sampling technique. The number of samples of this study was 54 respondents from the employees of KPP Pratama Makassar Utara in 2018. The sample is then processed by multiple linear regression analysis through classical assumption testing, coefficient of determination and hypothesis testing. Based on statistical tests using the SPSS 16.0 program, the determination coefficient value (R2) is 18.0%. Hypothesis test results show the perception of the ease of the user on the use of the Sistem Informasi Direktorat Jenderal Pajak (SIDJP) partially (t test) affects the performance of employees at KPP Pratama Makassar Utara. respondent's responses regarding user ease perception variables, respondents who agreed to 42 to 52 respondents and strongly agreed as much as 2 to 11 respondents. This shows that respondents were easy to use SIDJP. respondent's responses regarding perceptions of the usefulness of users, respondents who chose to agree with as many as 9 to 18 respondents, this indicates that respondents use SIDJP